Kualitas Audit Dan Faktor-Faktor Yang Mempengaruhinya (Studi Empiris Pada Kantor Akuntan Publik di Wilayah JawaTengah dan Yogyakarta) SKRIPSI - Handayani, Sri; , Drs. Muhammad Abdul Aris, M.Si (2016)
This research purpose to analyze the effect of independence, competence, due professional care, and accountability of the audit quality. this research was conducted by using survey method with questionnaire.This population used in this research is all of auditors who worked on the CPAs Office in Jawa tengah and yogyakarta . This research use purposive sampling in carry out sample selection. The data used in this research is primary data and data collection was performed using a questionnaire. The total sample collected as many as 41 questionnaire. Test statistic used is multiple linear regression test. The result of this research find type of the independence, competence, due professional care, and accountability are related significant influence with audit quality.